The influence of Dupuytren's disease fingers contracture degree on surgical treatment outcome - Stepić Nenad; Končar Jovana; Rajović Milica (Vojnosanitetski Pregled, 2017)
Background/Aim. Dupuytren’s disease is a progressive disease of the palmar and digital fascial structures, with functional limitations. There are no clear recommendations about the optimal time of surgical repair, concerning the hand impairment. The aim of our study was to investigate the relation between finger’s contracture degree and success of surgical treatment of the Dupuytren's disease. Methods. This prospective analysis included 60 patients operated on due to Dupuytren’s contracture. According to preoperative contracture degree of proximal interphalangeal (PIP) and metacarpophalangeal (MCP) joint, patients were divided into three groups: the group 1: < 15°, the group 2: 15−30° and the group 3: > 30°. All the patients underwent operation of partial palmar fasciectomy. Postoperative improvement was expressed with contracture reduction INDEX. Results. There were 60 patients with 85 fingers affected. The groups 1, 2 and 3 had 22 (37%), 37 (62%) and 26 (43%) fingers with MCP contracture and 32 (37.4%), 24 (28.2%) and 29 (34.1%) fingers with PIP contracture, respectively. Postoperative contractures of MCP joint in these groups were 0, 0.135° and 5°, and of PIP joint 0, 2.08 ° and 16.89°, respectively. After six months all MCP contractures resolved, while PIP joint contracture in the group 3 remained 13.62°. The reduction INDEX was 98.85%, 97.62% and 75.52% in the groups 1, 2 and 3, respectively. There was a statistically significant difference in the INDEX value between the groups (p = 0.0001). Conclusion. The degree of PIP joint contracture is related to the outcome of surgical treatment of Dupuytren’s disease. Optimal results are achieved when contracture degree is between 15° and 30°. Surgical treatment of MCP joint contracture is successful regardless of the preoperative joint contracture degree.